Improving Supercapacitor Energy Density via Nanocarbon Electrode Functionalization and Increasing Electrolyte Electrochemical Window. Issue 19 (14th March 2016) - Novikau, Uladzimir; Filipovich, Sviatlana; Razanau, Ihar
ABSTRACT: The present report is dedicated to a study of possible ways of increasing the energy density of the supercapacitor and thus, bridging the gap between the supercapacitor and the battery. Chemical functionalization of carbon nanomaterials, such as carbon nanotubes, activated carbon cloth, and activated carbon powder used as supercapacitor electrodes as well as novel aqueous electrolytes with the electrochemical window of up to 2 V are described. The hybrid approaches to energy storage mechanism in electrochemical energy storage devices are discussed. The first experimental results on the discussed hybrid energy storage devices are presented.